The Emergence of New Catalytic Abilities in an Endoxylanase from Family gh10 by Removing an Intrinsically Disordered Region - Levican-Jaque, G; Chavez-Rosales, R; Gil-Duran, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Endoxylanases belonging to family 10 of the glycoside hydrolases (GH10) are versatile in the use of different substrates. Thus, an understanding of the molecular mechanisms underlying substrate specificities could be very useful in the engineering of GH10 endoxylanases for biotechno-logical purposes. Herein, we analyzed XynA, an endoxylanase that contains a (β/α)8-barrel domain and an intrinsically disordered region (IDR) of 29 amino acids at its amino end. Enzyme activity assays revealed that the elimination of the IDR resulted in a mutant enzyme (XynA∆29) in which two new activities emerged: the ability to release xylose from xylan, and the ability to hydrolyze p-nitrophenyl-β-D-xylopyranoside (pNPXyl), a substrate that wild-type enzyme cannot hydrolyze. Circular dichroism and tryptophan fluorescence quenching by acrylamide showed changes in secondary structure and increased flexibility of XynA∆29. Molecular dynamics simulations revealed that the emergence of the pNPXyl-hydrolyzing activity correlated with a dynamic behavior not previously observed in GH10 endoxylanases: a hinge-bending motion of two symmetric regions within the (β/α)8-barrel domain, whose hinge point is the active cleft. The hinge-bending motion is more intense in XynA∆29 than in XynA and promotes the formation of a wider active site that allows the accommodation and hydrolysis of pNPXyl. Our results open new avenues for the study of the relationship between IDRs, dynamics and activity of endoxylanases, and other enzymes containing (β/α)8-barrel domain. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.